RESTRUKTURISASI ORGANISASI PADA SEKERTARIAT DAERAH KABUPATEN ENDE PROVINSI NUSA TENGGARA TIMUR - Pius Mithe; Heru Nurasa; Sawitri Budi Utami (Jurnal Public Policy, 2018)
This paper discusses the process of organizational restructuring that occurred at the Regional Secretariat of Ende District as a result of the policy of regional apparatus arrangement in Ende District, East Nusa Tenggara Province. Although it has gone through various changes, a number of regulatory tools have been replaced with the consequences of changing the concept of organizational restructuring from downsizing to rightsizing, but have not been able to significantly improve the performance of the Regional Secretariat of Ende District. In this study the author uses the concept of restructuring derived from the 4R theory (Gouilarrt & Kelly, 1995) with the indicators namely building an organizational model, integrating physical infrastructure, and redesigning the work architecture. The research method used is descriptive with a qualitative approach that is carried out through observation and interviews and reinforced secondary data studies from relevant agency documents and the results of previous competent research. The results show that indicators build economic models, integration of physical infrastructure, and redesign the work architecture have not run optimally. The restructuring was apparently not balanced with the availability of human resources and pre-facility facilities as well as good financial management . Keywords: Regional Secretariat of Ende District, Restructuring, Local Government Organization